Our experience of arteriovenous fistula creation as vascular access for hemodialysis - Sharma, Pradeep K.; Nagori, Rupesh; Baweja, Shekhar; Aggarwal, Vikas; Katti, Pawan; Chabbra, M. K. (International Surgery Journal, 2020)
Background: End stage renal disease (ESRD) patients depend on lifelong renal replacement therapy. The arteriovenous fistula (AVF) is the preferred hemodialysis access. Cimino fistulas are currently accepted as the best mode of vascular access for hemodialysis (HD). The present study was planned to study for presence of on table bruit and thrill and to know postoperative outcome and patency. Methods: This single center, prospective study was carried out in department of Urology at SNMC, Jodhpur from November 2018 to May 2019. Dominance of hand was examined, and preference was given to non-dominant hand. Physical examination of the arterial system along with physical examination of the venous system was done. Preoperative color Doppler of upper limb veins and arteries was done in selected patients. End to side anastomosis was done between cephalic vein and radial artery. Results: In this study of 70 cases of AVFs, there were 53 (75.71%) successful cases and 17 (24.2%) were failures. End (vein) to side (artery) anastomosis was done in 70 (100%) cases. On table bruit was present in 63 (90%) and thrill in 58 (82.8%) cases. All patients with failed post-operative fistula were not doing ball exercise. Conclusions: Presence of on table thrill and bruit are indicators of successful AVF. Post-operative ball exercise should be done for better results.